ANALYSIS OF PSYCHIATRIC NURSING CARE IN SCHIZOPHRENIC PATIENTS WITH APPLICATION OF OCCUPATIONAL THERAPY IN FREE TIME ACTIVITIES TO OVERCOME HALLUCINATIONS - Alfiya; Hidaayah, Nur; Fitriasari, Andikawati; Rohmawati, Riska (Universitas Nahdlatul Ulama Surabaya, 2024)
Introduction: Hallucinations are a mental health problem that is difficult to get rid of due to several factors such as socio-cultural where a person does not believe in his environment, causing anxiety and focusing on his hallucinations. Objective: This study examines the impact of occupational therapy in free time activities on schizophrenia patients experiencing hallucinations. The findings suggest that structured activities significantly reduce the frequency and intensity of hallucinations, improving overall patient well-being. The research highlights the importance of psychiatric nursing interventions in managing schizophrenia symptoms. Methods: The design used is a case study. Research subject Mrs. E is 50 years old in the flamboyant room of RSJ Menur with hallucinatory perception disorder nursing problems, free time occupational therapy (expressive writing and listening to music) is carried out 9 meetings with a duration of 30 minutes. The data collection instrument used mental health insurance sheets through observation techniques, interviews, and patient medical records. Results: The results of the study after the intervention of leisure occupational therapy (Expressive Writing and Listening to Music), show patients can write down their feelings in written form that cannot be expressed orally and can use spare time such as listening to music to provide a relaxing effect so that patients can control emotions and divert feelings the hallucinations. Conclusions: The use of leisure occupational therapy (Expressive Writing and Listening to Music) to reduce hallucinatory symptoms can be an alternative to fill the patient's spare time so that patients can divert their hallucinations and the relaxing effect of music can control the client's emotions from the effects of hallucinations, namely anxiety. In the future, it is hoped that in hospitals, especially flamboyant inpatient rooms, there will be SOPs for this therapy as a therapeutic option to reduce signs and symptoms of hallucinations.